EFFECT OF LIQUIDITY AND LEVERAGE ON FINANCIAL DISTRESS WITH PROFITABILITY AS AN INTERVENING VARIABLE - Sumarni S; Raykes Hinrich Tuerah; Christony Maradesa; Raymond Festus Rombot; Ruhiyat, Ruhiyat (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Financial Distress can be caused by a problematic economy in a company and cause economic instability in a company that can even lead to bankruptcy. This study aims to (1) determine the effect of liquidity, leverage, and profitability on financial distress (2) determine how profitability mediates the relationship between liquidity and leverage on financial distress. Research on all mining sector companies listed on the IDX for the 2017-2023 period. A population of 63 companies with a sample of 30 companies. The method used is purposive sampling. And the data analysis used is path analysis with SmartPLS 4.0 software. Based on the final results of this study, liquidity has a positive effect on financial distress, leverage does not affect financial distress, profitability has a positive effect on financial distress, liquidity does not affect profitability, leverage has a negative effect on profitability, then profitability is unable to mediate the effect of liquidity on financial distress, and profitability is able to mediate the effect of leverage on financial distress. The importance of financial distress analysis is to help management in making decisions to improve the company's financial situation faster before it gets worse, and so that external parties can invest in the company.